A Decade of Research on Intellectual Capital in Indonesia: Systematic Literature Review - Yuliana Kumalasari; Y. Anni Aryani (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
The present study aims to scrutinize empirical evidence related to the study of intellectual capital in Indonesia. The study conducts an analysis of 60 articles from Scopus-indexed and SINTA-indexed journals over the observational period spanning from 2012 to 2023. The methodology employed in this study is the charting field method. Notably, the findings reveal that financial performance serves as the predominant metric in the exploration of intellectual capital in Indonesia over the course of a decade. Nevertheless, our mapping results unveil a critical gap in the research landscape, specifically, the inconsistency in the relationship between intellectual capital and financial performance proxies such as Return on Assets (ROA), Return on Equity (ROE), Price-to-Book Value (PBV), and Debt-to-Equity Ratio (DER). It is our aspiration that future research concerning the subject of intellectual capital will extend their scope to non-financial performance dimensions and incorporate qualitative data analysis, surveys, interviews, or the incorporation of Environmental, Social, and Governance (ESG) indicators within the context of intellectual capital exploration in Indonesia.